Computational Thinking and Digital Literacy in Education: A Bibliometric Analysis and Systematic Literature Review of Educational Trends - Deitawati Dalughu; Susanti Kurniawati; Disman Disman (International Journal of Social Learning (IJSL), 2026)
This study aims to analyze the relationship between Computational Thinking (CT) and Digital Literacy (DL) in the context of education using a bibliometric approach combined with a Systematic Literature Review (SLR). Data were obtained from the Scopus database for the period 2020–2025 using targeted keywords and were systematically selected using the PRISMA framework. The analysis was conducted using RStudio and VOSviewer to comprehensively identify publication trends, patterns of researcher collaboration, and the development of relevant research themes. The results showed consistent publication growth, with an annual growth rate of 20.61% across 169 documents, accompanied by a significant increase in international collaboration. The synthesis of the 20 selected articles shows that CT and DL have a mutually reinforcing relationship in supporting students' development of critical thinking, problem-solving, and technological literacy. However, its implementation remains dominated in STEM and basic education, while in economic education, it remains limited, so broader, more adaptive contextual integration is needed for a sustainable future.